2014
DOI: 10.1186/1745-6215-15-49
|View full text |Cite
|
Sign up to set email alerts
|

Developing core outcomes sets: methods for identifying and including patient-reported outcomes (PROs)

Abstract: BackgroundSynthesis of patient-reported outcome (PRO) data is hindered by the range of available PRO measures (PROMs) composed of multiple scales and single items with differing terminology and content. The use of core outcome sets, an agreed minimum set of outcomes to be measured and reported in all trials of a specific condition, may improve this issue but methods to select core PRO domains from the many available PROMs are lacking. This study examines existing PROMs and describes methods to identify health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
133
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(134 citation statements)
references
References 86 publications
0
133
0
1
Order By: Relevance
“…The selection of instruments will be focused on those that have demonstrated adequate measurement properties for these domains with the least participant burden. Recently published methodological guidance on this topic [46,47] will help to conduct the next step for this COS in NSLBP.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of instruments will be focused on those that have demonstrated adequate measurement properties for these domains with the least participant burden. Recently published methodological guidance on this topic [46,47] will help to conduct the next step for this COS in NSLBP.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of a set of core outcome measures to be included in future research, via wellestablished methodology to determine the inclusion of patient-reported outcomes (Macefield 2014) …”
Section: Implications For Researchmentioning
confidence: 99%
“…Psychometric evaluations reveal that many scores can be used to measure changes in disease status (high sensitivity to change) with high reproducibility in patients (high intraindividual reliability). However, they can be heavily confounded by patient perception and vary significantly between patients (high interindividual variability) [2]. For example, 5,000 steps per day can result in a very high subjective score of an elderly lady shortly after a hip fracture.…”
Section: The Needmentioning
confidence: 99%